A Practical Synthesis of Ammonia from Nitrogen Gas, Samarium Diiodide and Water Catalyzed by a Molybdenum–PCP Pincer Complex - Ashida, Yuya; Kondo, Shoichi; Arashiba, Kazuya; Kikuchi, Takamasa; Nakajima, Kazunari; Kakimoto, Seizo; Nishibayashi, Yoshiaki (Synthesis, 2019)
A practical method for ammonia synthesis is described. The reaction of atmospheric pressure of nitrogen gas with samarium diiodide as a reducing reagent and water as a proton source in the presence of a catalytic amount of a molybdenum trichloride complex bearing a PCP [1,3-bis(di-tert-butylphosphinomethyl)benzimidazol-2-ylidene]-type pincer ligand occurs under ambient conditions to afford ammonium sulfate after treatment with sulfuric acid.
Keywords: ammonia; dinitrogen; molybdenum; samarium diiodide; water